424Person-centred outcomes among 22, 205 cancer survivors and 244, 000 people without cancer: a population-based Australian study. (2nd September 2021) - Joshy, Grace; Thandrayen, Joanne; Koczwara, Bogda; Butow, Phyllis; Laidsaar-Powell, Rebekah; Rankin, Nicole; Canfell, Karen; Stubbs, John; Grogan, Paul; Banks, Emily
Abstract: Background: With the majority of people with cancer surviving long-term, holistic consideration of health and wellbeing outcomes is critical to optimise survivorship. We quantified short- and long-term physical and mental health-related outcomes in people with and without cancer, including according to cancer type and clinical characteristics. Methods: 45 and Up Study (n = 267, 153) baseline survey data (2006-2009) were linked to cancer registrations (by the Centre for Health Record Linkage) and cancer diagnoses up to enrolment identified. Modified Poisson regression estimated age-and-sex-adjusted prevalence ratios (PRs) for adverse person-centred outcomes - severe physical functioning limitations, moderate/high psychological distress and fair/poor quality of life - in participants with versus without cancer. Results: Cancer survivors (n = 22, 205) had significantly higher prevalence of physical functioning limitations compared to participants without cancer (21% versus 13%) PR = 1.28(95%CI=1.25-1.32), overall and in all population subgroups examined. Corresponding estimates were 22% versus 24% (1.05(1.02-1.08)) for psychological distress and 15% versus 10% (1.28(1.24-1.32) for fair/poor quality of life. Outcomes varied by cancer type, being worse for multiple myeloma, lung cancer and non-Hodgkin's lymphoma; worse outcomes were also associated with recent diagnosis, recent treatment and advanced stage. Physical functioning limitations in cancer survivors were major contributors to adverse distress and quality of life outcomes. Conclusions: Cancer survivors experience adverse physical and mental health outcomes; substantial parts of elevated distress and poor quality of life are likely attributable to physical disability. Key messages: In addition to routine screening for psychological distress, management of physical disability and other symptoms are important to optimise cancer survivorship.